APPLICATION JUST IN TIME METHOD WITH TRADITIONAL METHOD IN ENHANCING EFFICIENCY COST OF RAW MATERIALS: (STUDY ON UD. SIDO RUKUN) - Rumanintya Lisaria Putri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
This study aims to find out the methods of Just In Time and traditional methods In Efforts to Increase Cost Efficiency of Raw Material Supply As A Smoothness of Production Process can be applied to UD. Sido Rukun. The object of this research is UD. Sido Rukun which is located at Jl. Garuda Umbul Damar-Binangun - Blitar. The analytical tool used in this study is descriptive qualitative analysis, where the authors do not use the elements of numbers, but done by expressing descriptions and explanations, and methods used in this study is qualitative. Namely using primary data and secondary data, data collection techniques using interviews, observation and documentation. And the variables used in this research are inventory, JIT, supplier and cost efficiency. From the results of the analysis it can be seen the results of a traditional calculation of Rp. 10.892.328.903 while the result from just in time is Rp. 9.669.765.400 , - so the company can save the cost of raw materials inventory of Rp. 1.222.563.503, -